Identification and Antibiogram Assay of Escherichia Coli Isolated From Chicken Eggs (Journal of Bio-Science, 2021)
Chicken eggs contain all the essential components such as proteins, lipids, vitamins, minerals, carbohydrates, and growth factors required by the human being. Despite of their nutritional values eggs can cause health problems through consumption of contaminated eggs with pathogenic microorganisms. Therefore, the present study was undertaken to identify Escherichia coli isolated from chicken eggs with their antibiogram assay in Rajshahi district of Bangladesh. E. coli was isolated from 180 chicken eggs collected from different areas of Rajshahi district and identified based on cultural, staining, and biochemical characteristics. Antibiogram assay of all the isolates were done by disk diffusion method. The overall prevalence of E. coli was 38.89% in chicken eggs of which 27.78% was on egg shells and 11.11% was in egg content. The prevalence of E. coli was 58.33% in commercial layer farm eggs, 41.66% in whole seller eggs, and 16.67% in retailer eggs. In antibiogram study, isolated E. coli showed 64.28% to 92.85% sensitivity to chloramphenicol, gentamycin, and ceftriaxone. The highest sensitivity was found to meropenem (100%). Isolated E. coli showed resistance to ciprofloxacin, tetracycline, amoxicillin, ampicillin, and erythromycin ranging from 50% to 71.42%. Judicious use of antibiotics and public awareness will help to reduce the development of antibiotic resistance.J. Bio-Sci. 29(1): 123-133, 2021 (June)